Simultaneous determination of fluoride, acetate, formate, chloride, nitrate, and sulfate in distilled alcoholic beverages with ion chromatography/conductivity detector - Güler, Melike; Destanoğlu, Orhan; Gümüş Yılmaz, Gülçin (The Turkish Chemical Society, 2020)
A novel ion chromatography with suppressed conductivity detection method was developed for simultaneous determination of fluoride, acetate, formate, chloride, nitrate, and sulphate in distilled alcoholic beverages. In this study, bromide was used as an internal standard. The separation of the anions was accomplished by utilising an anion exchange column with gradient eluent program. The chromatographic conditions were as follows: the suppressor current was 31 mA; the flow rate of the mobile phase was 0.25 mL min-1; the column and detector compartment temperature were 35 °C and 40 °C, respectively; sample loop volume was 10 μL. All the calibration curves showed good linearity (r2 ≥ 0.999). The limits of detection (LOD) values were between 0.56 and 13.2 μg L-1 while the limits of quantification (LOQ) values were between 1.80 and 43.9 μg L-1. To evaluate the accuracy, a raki sample was spiked with standard solutions at three different concentration levels and the average recoveries were found in the range of 94.90% - 101.71%. Intra-day and inter-day precision studies were also investigated and the relative standard deviations (RSDs %) were less than 5.99%. The validated method was applied to the three kinds of commercial samples: Turkish raki, vodka, and gin.
Keywords: Ion chromatography; anion analysis; distilled alcoholic beverages; Analitik Kimya; Analytical Chemistry